Heterogeneity of outcomes in randomized controlled trials on implant prosthodontic therapy is hindering comparative effectiveness research: meta-research study - Ante Vardić; Livia Puljak; Tea Galić; Joško Viskić; Ena Kuliš; Tina Poklepović Peričić (BMC, 2023)
Abstract Background Consistency in outcomes across clinical trials allows for comparing and combining results from different studies. A core outcome set (COS), representing a minimally agreed standardized group of outcomes that should be monitored and measured through research in a specific field of medicine, is not yet available for trials in implant prosthodontic (dental implant) therapy. This meta-research study aimed to analyze outcomes used in clinical trials on implant prosthodontic therapy. Methods We searched the Cochrane Oral Health Group (COHG) register to identify systematic reviews of interventions in implant prosthodontic therapy published by October 2023. From the randomized controlled trials (RCTs) included in the relevant reviews, we extracted data on the characteristics of the included trials and the outcomes used. We categorized outcomes into domains. Results From 182 systematic reviews in the COHG register, we included 11 systematic reviews on dental implant therapy. The reviews included 117 unique RCTs with 4725 participants, published from 1995 to 2020, which analyzed 74 different outcomes. Using different definitions, implant failure was analyzed in 73 RCTs. Seventeen RCTs did not define implant failure. Failure was most often (30 RCTs) followed up for one year. Only one RCT assessed implant failure after five years. Trials used 17 definitions of implant failure, while 17 trials did not report on the criteria of implant failure. Complications were analyzed in 48 RCTs, although they were not clearly defined in 12 RCTs. Failure of prosthodontic supra-structure was analyzed in 74 RCTs, with definitions of failure and criteria not clearly defined in 44 RCTs. Trials considered adverse events, peri-implant tissue health, patient attitudes, and other outcomes, including cost, aesthetics, or procedure duration. These outcomes were often different between trials. Twenty-six outcomes were used only once per study. Conclusions Clinical trials in implant prosthodontics used different outcomes, different definitions of outcomes and used different times to monitor them. Standardization of outcomes is necessary to allow comparability and evidence synthesis about the effectiveness of implant prosthodontic therapy.